Teacher’s Obstacles in English Online Learning during Covid-19 Pandemic - Yoga Purnama (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
The study investigated some difficulties on the implementation of learning English through online learning due to Covid-19 pandemic on students from Islamic Family Law of IAIN Surakarta in the academic year of 2020/2021. The type of this research is qualitative descriptive. The data in this study are learning problems that occur in English language online learning activities. The data collection technique was carried out by documentation techniques and observations. Data analysis used in this research is data collection, data reduction, data presentation and conclusion. The study found that there are three main difficulties which hinder English language teaching and learning process namely: (1) student’s limited skills of English, (2) lack of teacher supervision and interactions during the learning process, and (3) inadequate learning facilities and internet networks for online learning. The right implementation of learning strategy, communication, patience, and consideration on students’ condition become the key factors to overcome all the problems during online learning in pandemic era.